Monitoring parameters of technical condition and safety of aircraft using control charts - Чепіженко, В.І.; Добриденко, О.М.; Самотьос, В.М.; Волков, В.О. (Proceedings of National Aviation University (archive), 2007)
The opportunity of control cards use for monitoring of a technical condition parameters and reliability of aviation techniques is considered at its operation on a technical condition.